Penerapan Konsep Rahmatan Lil 'Alamin sebagai Strategi Pencegahan Kekerasan di Lingkungan SMK Islam Kanigoro Blitar - Desy Anindia Rosyida; Ida Putri Rarasati; Nadya Putri Kartikasari (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to examine the implementation of the Rahmatan Lil Alamin concept as a character education approach in preventing violence at SMK Islam Kanigoro Blitar. The Rahmatan Lil Alamin concept, which encompasses values of compassion, tolerance, justice, and peace, is highly relevant for preventing various forms of violence in the school environment, including verbal, physical, and psychological violence. This research uses a descriptive qualitative approach with data collection techniques such as observation, in-depth interviews, and documentation. The subjects of the study include teachers, students, and school staff. The focus of the research is on the school's strategies in applying Islamic values of Rahmatan Lil Alamin, the types of violence that occur, and the impact of internalizing these values on student behavior. The findings show that the implementation of the Rahmatan Lil Alamin concept at SMK Islam Kanigoro is carried out through the reinforcement of Islamic school culture, habituation of positive behaviors, and integration of values of compassion and tolerance in learning. Furthermore, the support of the entire school community is essential in creating a safe and comfortable learning environment. This approach has proven effective in reducing incidents of violence and raising student awareness of the importance of mutual respect and maintaining peace. This study is expected to contribute to the development of Islamic education, particularly in designing violence prevention strategies based on noble Islamic values that are applicable in educational institutions.